A pragma-semiotic analysis of 'Occupy Nigeria Group' online posts on the 2012 fuel subsidy removal in Nigeria. Issue 3 (2nd July 2016) - Igwebuike, Ebuka; Abioye, Taiwo; Chimuanya, Lily
Abstract: In response to the fuel subsidy removal by the Nigerian government on 1st January 2012, Occupy Nigeria Group, a protest movement, embarked on different mass strike actions and demonstrations including online activism. The civil resistant actions geared towards reversal of petrol pump price increase deployed certain verbal and visual means in portraying the government and its actions. Previous studies on online protest discourse in Nigeria have adopted sociolinguistic and discourse analysis approaches in examining issues of identity and self-determination with little attention paid to visual-pragmatic strategies in representing people and their actions. This article, therefore, undertakes a pragma-semiotic investigation of 'Occupy Nigeria Group' online posts on the 2012 fuel subsidy removal in Nigeria with a view to examining verbal and visual modes of representing people and their actions in the event. Seventy-two online protest posts purposively sampled from the groups' page are used to identify and categorize various pragma-semiotic elements and functions in the representations using insights from Mey's (2001) pragmatic act and Kress and van Leeuwen's (2006) multimodal discourse analysis. It is observed that the verbal mode complements the visual in projecting the demands and resistance of the group. The posts which are classified under six semantic fields, namely divine intervention, security consciousness, innovation, exaggeration, defamation and abusive placards have various visual-pragmatic strategies such as prayer, negative labelling, humour, mockery, abuse, passionate and fierce appeal, including photo trick. The strategies correspond to the dominant pragmatic acts such as demonstrative, assertive, suppository, condoling and stipulating. All these acts are presented within the Nigerian socio-political and linguistic context.